ECLAMPSIA AND ITS ADVERSE MATERNAL AND PERINATAL OUTCOMES: AN ANALYSIS AT A TERTIARY CARE HOSPITAL - Maimoona Qadir (Journal of University Medical & Dental College, 2017)
ABSTRACT: BACKGROUND: Eclampsia is a major public health problem, associated with maternal and perinatal morbidity and mortality. Its treatment needs multi disciplinary approach. OBJECTIVE: To determine maternal and perinatal outcomes of eclampsia in patients attending Khyber Teaching Hospital, Peshawar. METHODOLOGY: This prospective cross sectional study was conducted at Gynaecology and st stObstetrics Department of Khyber Teaching Hospital, Peshawar from 1 January, 2015 to 31 December, 2015. All women of any age or parity with history of seizures after 20 weeks and within 48 hours post partum were included. Detailed history including age, parity, period of gestation, antenatal care, vomiting, epigastric pain, vomiting, pain, visual disturbances, edema, headache and details of seizures were taken. After detailed examination and investigations, all ﬁndings were recorded in predesigned proforma and data analyzed. RESULTS: Incidence of eclampsia was 1.5%, with antenatal eclampsia being present in 55.7% cases. The most prevalent age group was 15-25 years where 61% of our patients fell, followed by 26- 35 years age group. Sixty two percent were primigravidas, and 78.7% cases were non booked. Cesarean section was common mode of delivery in 52% subjects. Acute renal failure and pulmonary edema were seen in 7% cases each, followed by cerebrovascular accidents in 6% and HELLP syndrome, coagulopathy and prolonged unconsciousness in 5% cases each. Perinatal mortality rate was 25.3% and most common fetal morbidity was birth asphyxia in 33%, low birth weight in 23%, NICU admission in 18.58%. Early neonatal deaths were observed in 5.3% and stillbirth rate was 20%. CONCLUSION: To combat eclampsia, active participation of community, doctors, governmental and non governmental organizations is needed. Perinatal care, health education, training in eclampsia management and timely referral are the strategies for control of this public health problem.